Stent Selection in Preoperative Biliary Drainage for Patients With Operable Pancreatic Cancer Receiving Neoadjuvant Therapy: A Meta-Analysis and Systematic Review - Du, Jianbing; Gao, Xiangyu; Zhang, Hongtao; Wan, Zhuo; Yu, Hengchao; Wang, Desheng (Frontiers in Surgery, 2022)
With the increasing use of neoadjuvant therapy (NAT) in patients with pancreatic cancer to reduce tumor burden on prognosis, preoperative biliary drainage (PBD) is becoming increasingly necessary. The aim of this study was to summarize the latest evidence and compare the clinical efficacy of metal stents (MS) and plastic stents (PS) in patients undergoing neoadjuvant therapy for operable pancreatic cancer. Eligible studies were searched in PubMed, Embase and Cochrane Library from their inception to September 2021. In this study, RevMan 5.4 was used to perform the analyses. Two randomized controlled trials (RCTs) and six retrospective studies with 316 patients were included. All patients had pancreatic cancer and received NAT before surgical resection. Meta-analysis showed that the rate of endoscopic reintervention in MS (26/143, 18%) group was lower than that of PS (122/153, 80%) group (P < 0.05). The rate of stent-related complications in MS group was lower (18/118, 15%) than that of PS (52/117, 44%) group (P = 0.02). But there were no significant differences in operative time, operative blood loss, overall postoperative complications, postoperative hospitalization days and total medical costs between the two groups. For operable pancreatic cancer patients undergoing NAT surgery, MS was preferred over PS in terms of the incidence of endoscopic reintervention and stent-related complications. More clinical trials are needed in the future to confirm these data with higher levels of evidence.